Rural Development Strategy of the Northern Region - Lazhentsev, Vitaliy N.; Ivanov, Valentin A. (Economy of Regions, 2020)
The paper aims to analyse methodological approaches to the development of rural areas, considering the environmental and economic conditions of the North. We claim that, from a social perspective, the sectoral approach based on the agricultural production policy is ineffective. It is advisable to apply an integrated approach. It considers rural development as a process of improving the life of the population who is directly related to the use of land and other biological resources included in the system of the geographical division of labour and related social relations. This study not only analyses production indicators but also assesses the potential and efficient use of rural areas and households. They include homesteads, public infrastructure, municipal infrastructure in rural (and partially urban) settlements and settlement systems, and natural landscapes with certain social and economic functions. The example of the Komi Republic demonstrates underutilisation of the rural natural resources and labour potential, an extremely small investment in rural infrastructure, and low living standards of the rural population. To improve the situation in the Republic, it is necessary to develop agriculture and assess its strategic trends, considering the objective need to increase the self-sufficiency of the population with crop and livestock products. Other directions for development are the diver- sification of the rural economy and its landscape adaptation; the strengthening of the relations between agriculture, forestry and developing manufacturing industry; the establishment of new relations in the agricultural sector following the «city — village» line. Moreover, it is essential to preserve the Northern ethnic culture and traditional economic activities and introduce environmental services into the economic specialisation of municipalities. The mechanisms for implementing these directions include innovative modernisation of rural spatial and economic systems, as well as tools for regulatory, organisational, and financial support of rural production and life that considers its Northern specifics. We identified a set of directions and mechanisms of strategic planning. Comparison of rural development with the officially adopted agricultural strategies and programmes revealed that they differ significantly, especially in social and territorial aspects. It is necessary to eliminate this significant gap in the spatial development planning for improving the living standard of the rural population.